PENGARUH BUDAYA ORGANISASI, IKLIM ORGANISASI DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT MEDIA UTAMA - kasnowo kasnowo (PROFIT, 2018)
A company or organization, Managing human resources is one of the least organisasi.management functions depending on the organization's management performance kberhasilan manajmn in the manage resource. Therefore, the challenge is how to build strategic management of human resources as well.A organization can not move without the vision and mission of the employee.for this study aims to examine the influence of organizational culture, organizational climate, and promotions can influence job satisfaction in PT Media Utama. Object in this research are 64 employees, using multiple linear regression analysis proved that the hypothesis is suspected of Organizational Culture, Organizational Climate and Job Promotion effect on employee job satisfaction is received with a value of determination (R2) = 0.712 or 71.2% of the three variables above calculation turns organizational Climate variables have the strongest effect (dominant) which is supported by the results of r = -.346 later culture of the organization with the result r = -.255 and Promotions with the result r = -.